Soybean Cost-Return Budget in Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Ibendahl, Gregg (My University, 2015)
This publication projects a budget that reflects expected income and costs based on typical soybean production practices in northeastern Kansas.
MF570_2015_04
Keywords: MF570; Economics; Crops; MF